Comparative Effects of Distance Learning Education Programme and Classroom Based Instruction on the Learning Behaviour of Students in Nigeria - Akanle, Florence Foluso; Ofie, Lami (NIU Journal of Social Sciences, 2018)
The study investigated (two instructional strategies) the comparative effectiveness of distance learning educational experiences and the classroom-based instruction on the learning behaviour of matured students in the distance learning programme in Ado Ekiti study center of Ekiti State University Nigeria. A pre test post test experimental research design was adopted for the study. The population comprised of about 1000 student in the study center of Ado-Ekiti distance learning center. The subjects were 40 undergraduates. A 2 x 2 factoral design was used for the study. 20 students were randomly selected and assigned to each of the two groups. The data was collected using the learner observation sheets, a validated and reliable research instrument. Treatment consists of the exposure to the counseling and independent content (CIC) of a training package using the traditional classroom based instruction and the distance education learning approach. Two research hypotheses were formulated to guide the study. The hypotheses were tested using (ANOVA). The study revealed that student learning behaviour became relatively effective as a result of distance learning education. The study demonstrated that distance learning consistently develops a positive effect on students learning behaviour, improve their study skills and learning strategies. Appropriate recommendations were made.